The spooky art thoughts on writing - Mailer, Norman 1923-2007 (Random House, 2003)
In [this book, the author] discusses with signature candor the rewards and trials of the writing life, and recommends the tools to navigate it. Addressing the reader in a conversational tone, he draws on the best of more than fifty years of his own criticism, advice, and detailed observations about the writer's craft. [He] explores, among other topics, the use of first person versus third person, the pressing need for discipline, the pitfalls of early success, and the dire matter of coping with bad reviews. While [the book] offers a ... preview of what can lie in wait for the student and fledgling writer, [it] also has a great deal to say to more advanced writers on the contrary demands of plot and character, the demon writer's block, and the curious ins-and-outs of publishing. Throughout, [the author] ties in examples from his own career, and reflects on the works of his fellow writers, living and dead -- Twain, Melville, Faulkner, Hemingway, Updike, Didion, Bellow, Styron, Beckett, and a host of others.-Dust jacket.
Keywords: Mailer, Norman; Mailer, Norman -- 1923-2007; Authorship; Fiction -- Authorship